Characterization of pyruvate dehydrogenase complex E1 alpha and beta subunits of Mycoplasma synoviae. (June 2021) - Bao, Shijun; Ding, Xiaoqin; Yu, Shengqing; Xing, Xiaoyong; Ding, Chan
Abstract: Mycoplasma synoviae (MS) is an important pathogen which causes huge economic losses to the poultry industry worldwide, and research on MS can provide the foundation for diagnosis, prevention, and treatment of MS infection. In this study, primers designed based on the sequences of pyruvate dehydrogenase complex (PDC) E1 alpha and beta subunit genes ( pdhA and pdhB, respectively) of MS 53 strain(AE017245.1) in GenBank were used to amplify the pdhA and pdhB genes of MS WVU1853 strain through PCR. Subsequently, the prokaryotic expression vectors pET-28a(+)-pdhA and pET-28a(+)-pdhB were constructed and expressed in Escherichia coli BL21(DE3) cells. The recombinant proteins rMSPDHA and rMSPDHB were purified, and anti-rMSPDHA and anti-rMSPDHB sera were prepared by immunizing rabbits, respectively. Subcellular localization of PDHA and PDHB in MS cells, binding activity of rMSPDHA and rMSPDHB to chicken plasminogen (Plg) and human fibronectin (Fn), complement-dependent mycoplasmacidal assays, and adherence and adherence inhibition assays were accomplished. The results showed that PDHA and PDHB were distributed both on the surface membrane and within soluble cytosolic fractions of MS cells. The rMSPDHA and rMSPDHB presented binding activity with chicken Plg and human Fn. The rabbit anti-rMSPDHA and anti-rMSPDHB sera had distinct mycoplasmacidal efficacy in the presence of guinea pig complement, and the adherence of MS to DF-1 cells pretreated with Plg was effectively inhibited by treatment with anti-rMSPDHA or anti-rMSPDHB sera. These findings indicated that surface-associated MSPDHA and MSPDHB were adhesion-related factors of MS and that the binding between MSPDHA/MSPDHB and Plg/Fn contributed to MS adhesion to DF-1 cells. Highlights: M. synoviae pyruvate dehydrogenase complex E1 alpha and beta subunits were new adhesins which can facilitate specific attachment to DF-1 cells. M. synoviae pyruvate dehydrogenase complex E1 alpha and beta subunits were identified to be distributed between the cell membrane and the cytoplasm. Antiserum to Recombinant E1 alpha or beta subunits could kill M. synoviae in an in vitro complement assay. Recombinant E1 alpha or beta subunits specifically bound to chicken Plg or human Fn in a dose-dependent manner.